2020
DOI: 10.1186/s12913-020-05725-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of routine use of radiography in patients with ankle fractures leads to lower costs and has no impact on clinical outcome: an economic evaluation

Abstract: Background To evaluate the cost-effectiveness of a reduction in the number of routine radiographs in the follow-up of patients with ankle fractures. Methods We performed an economic evaluation alongside the multicentre, randomised WARRIOR trial. Participants were randomised to a reduced imaging follow-up protocol (i.e. radiographs at week 6 and 12 follow-up obtained on clinical indication) or usual care (i.e. routine radiography at weeks 6 and 12). The Olerud & Molander Ankle Score (OMAS) was used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A total of 476/546 studies were excluded after the full‐text review ( n = 34; Supplementary Digital File ). After final screening, we included 70 studies, 22‐91 but no data on primary outcomes were reported in three of these 26,67,91 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 476/546 studies were excluded after the full‐text review ( n = 34; Supplementary Digital File ). After final screening, we included 70 studies, 22‐91 but no data on primary outcomes were reported in three of these 26,67,91 …”
Section: Resultsmentioning
confidence: 99%
“…Most studies were based on case series ( n = 33) 22,31,33,34,36,38,41,43‐50,56,57,60‐64,66,68‐72,74,75,77,85,89,90 followed by systematic reviews with or without meta‐analysis ( n = 12), 23‐25,28,29,39,53,59,67,78,83,86,88,91 prospective cohorts ( n = 9), 30,32,35,37,42,51,54,79,87 RCTs ( n = 9) 27,55,65,73,80‐82,84 and retrospective cohorts ( n = 2; Supplemental Digital File ) 52,58 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations